Pengaruh pemberian ekstrak buah jeruk purut (citrus hystrix) dan lama pengasapan terhadap sifatorganoleptik, kandungan protein dan lemak daging se’i babi - Ediyanto Pati Mayi; Pieter R. Kale; Geertruida M. Sipahelut (Jurnal Peternakan Lahan Kering, 2019)
The purpose of this research is to know the effect of citrus fruit extract on aroma, taste, tenderness, protein content, and fat content of Se'i pork. The method used in this research is Randomized Complete Random Design (RAL) with factorial pattern with 4 levels of kaffir lime extract as Factor A and 3 methods of fumigation as Factor B. Each treatment combination is repeated 3 times. Treatment of kaffir lime level is: a0 = control (without giving of kaffir lime extract), a1 = 1% orange extract, a2 = 2% orange extract, a3 = 3% citrus lime extract. Fresh Smoking Treatment: b1 = 30 min, b2 = 60 min, b3 = 90 min. Organoleptic variable in the test that is used 4 criteria that is aroma, taste, color and tenderness. The data obtained will be analyzed by non Kruskall Wallis test metric analysis followed by Mann Whitney test while the fat content, and protein are analyzed by Variety analysis and followed by Duncan multiple range test. The result of statistical analysis showed that the treatment had significant effect (P <0,05) to aroma, taste, color, tenderness, protein content and fat content.